(3eYGgO GdJfUjU Ydi ThGgO GdJdNjUs - (3YHO GdQMje Hf YHO GdQMef Hf CMeO GdYHGOj GdYHGSj, Rjf GdOjf,J (B963 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMeO ddg GdPi CWdY ai SeGA GdHjGf CgdgI GdeYGfi , hCHOY HHOjY GdEYLGR BjGJ GdeKGfi , hLdGLjO GdCOH HCSQGQ GdHdGZI hHYO aEfi de CRd eP fjWJ Yf JeGFe GdHfhI , hCJjWJ Hi ceGFe GdaJhg eJeSckG HCPjGd GdYde hCQcGfg s
(3BNQgG (B:s
(3dGRGd ef SWQ PG HGSeg jHbi HbGA Gdadc GdOGFQ hef jfGhFg jYT HGFSkG jSMH Pjd GdNGSF GdNGSQ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B345 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B563s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1730s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs